(untitled) (REMUNOM, 2025)
This article presents an interdisciplinary teaching proposal that connects the contents of Physics and Mathematics through the use of the Tracker software, aiming to understand the motions of free fall and projectile launch associated with the study of quadratic functions. The research was conducted with students from the 1st year of high school at a public school in the municipality of Boqueirão-PI, using both qualitative and quantitative approaches. Pre-tests and post-tests were carried out to assess students’ knowledge, along with practical activities involving video analysis and a perception questionnaire. The results show progress in students’ learning regarding the relationship between mathematical and physical concepts, such as the vertex of a parabola and the trajectory of moving bodies. The use of Tracker contributed to learning by arousing students’ interest and facilitating the development of investigative skills. It is concluded that the use of technological resources in the teaching of functions, combined with mathematical modeling and interdisciplinary practice, becomes a potential enhancer in the teaching-learning process. Keywords: Quadratic function; Free fall; Projectile motion; Interdisciplinarity; Tracker.